Estudio de factibilidad para la creación de una revista informativa en el Gad del cantón el Empalme, año 2014. - Romero Cevallos, Jonathan German (2015)
This research entitled "Feasibility study for the creation of an information magazine on the GAD Canton El Empalme, 2014", has been developed methodologically, diagnosing the current situation of the citizens living uninformed of the activities of Mr. ago mayor in improving the canton. Aims to determine the financial, economic and technical feasibility for the implementation of an information magazine on the activities developed for the benefit of the citizens of Canton in order to contribute to development of Good Living. This magazine is intended to contribute to improving the information space of the Autonomous Government Decentralization, ie, no, just, be adults that are reported, but also the children, so that in this way do not miss the customs of our ancestors that shaped the development of the canton. For GAD is very important this magazine, seen, that it will keep the community informed of all aspects inherent to the council. For the implementation of this project will have the support of the mayor, which has a total investment of $ 21,252.70; a NPV of $ 28,892.08 and an IRR of 63%.